Data on the epidemiology of heart failure in Sub-Saharan Africa - Ulrich Flore Nyaga; Jean Joel Bigna; Valirie N. Agbor; Mickael Essouma; Ntobeko A.B. Ntusi; Jean Jacques Noubiap (Data in Brief, 2018)
In Sub-Saharan Africa (SSA), chronic non-communicable diseases and cardiovascular diseases in particular, are progressively taking over infectious diseases as the leading cause of morbidity and mortality. Heart failure is a major public health problem in the region. We summarize here available data on the prevalence, aetiologies, treatment, rates and predictors of mortality due to heart failure in SSA. Keywords: Heart failure, Prevalence, Aetiologies, Treatment, Mortality, Sub-Saharan Africa